The competition and changes of masculinity images in the integration process of East and West: The case study of East and West Germany - Brandes, Holger (Socialinė teorija, empirija, politika ir praktika, 2006)
The images of masculinity between East and West Germany are compared. The author uses the theory of Robert Connell for the conceptualisation of masculinity. The interview method was used for data collection. The results of data analysis show that there are hegemonic images of masculinity. The hegemonic masculinity image of East Germany is hero of work and the hegemonic masculinity image of West Germany is workaholic. The revealed images are discussed in the context of gender antagonism and equality. The results suggest that the West Germany hegemonic masculinity image establishes in the East. Also, author discuses the expansion of West Germany masculinity image into the East Europe and Lithuania.
Keywords: Masculinity; Robert Connell; Germany